Assessment on liver function biomarkers in HIV positive pregnant and Non-pregnant women on Antiretroviral therapy in Rivers State, Nigeria - Odinga Tamuno-Boma; Azuonwu Obioma; Opusunju Boma Harris; Tee Popnen GP; Gabriel-Brisibe Christine Umanu; Ihua Nnenna; Akuru Udiomine Brantley; Akram Muhammad (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2023)
Background: The use of Antiretroviral Therapy (ART) has greatly improved the health and lifespan of people living with HIV, however, hepatic dysfunction has been associated with HIV. This study investigated the liver function biomarkers of women living with HIV and who are on ART.  Methods: A cross-sectional study was conducted on HIV-positive pregnant women and HIV-positive non-pregnant women in Rivers State, Nigeria. A total of 330 women between 15-60 years participated in this study. HIV-negative pregnant and non-pregnant women served as a control to the test subjects. Sociodemographic data were collected using a well-structured questionnaire. Blood samples were collected for biochemical assay of the liver function biomarkers. The subjects were on Tenofovir-Lamivudine-Efavirenz (TLE) antiretroviral therapy. Data were analyzed statistically on IBM SPSS Version 25 using student's t - test, ANOVA and compared using the Post hoc test. Results: The results obtained showed a significant increase at p ≤ 0.05 in the ALP, ALT and AST levels of both HIV-positive pregnant and non-pregnant women when compared to the control group. The serum TP level of HIV-positive pregnant women decreased in comparison to the control group. However, the decrease was not statistically significant at p ≤ 0.05. A statistically significant increase in the total protein level was observed in the HIV-positive non-pregnant women when compared to the control group. The albumin level in HIV-positive pregnant women had a statistically insignificant increase in comparison to the control group. HIV-positive non-pregnant women had a decreased level of Albumin at p ≤ 0.05 in comparison to the control group. Conclusion: The findings of the study suggest that the HIV-positive pregnant and non-pregnant women on ART are prone to adverse alterations in their liver function biomarkers in comparison to the control groups, hence they are vulnerable to liver dysfunction. Thus proper care and regular investigations should be carried out on HIV-positive women on ART.